Pneumaturia and Colonic Bleeding Post-Inguinal Herniorrhaphy: A Case Report - Raymond A. Dieter (Uro, 2024)
Introduction: A 51-year-old male was seen complaining of pneumaturia and bowel complaints, including blood per rectum. The patient related a history of an open left inguinal hernia repair utilizing a Kugel mesh ten years before. Case Presentation: Cystoscopy and colonoscopy demonstrated a hemorrhagic mass due to a prosthetic mesh protruding into the bladder and colon. Following colonoscopy and cystoscopy, a large inflammatory mass involving both the colon and urinary bladder was resected, which contained a rolled-up “tubular” mesh structure. After primary repair of the urinary bladder and placement of a Foley catheter, the sigmoid colon and mesh were resected, and the colonic anastomosis was completed. Outcome: Postoperatively, the patient progressed well with normal colon and bladder function after the removal of the Foley catheter. Discussion: Historically, the patient demonstrated the risk of major multiorgan surgical complications of a newer inguinal hernia repair technique, which may occur even a decade or more after the initial surgical correction and is, therefore, presented.